A Descriptive Study of Operational Data for a Novel Early Psychosis Intervention Program for Youths Aged 12–18 - Chee Hon Chin; Li Keat Oon; Charmaine Tang (BJPsych Open)
Aims: The Early Intervention in Psychosis (EPIP) team in Singapore extended its remit to see 12–15-year-old patients presenting with diagnosed psychosis (not ARMS) in 2019. This program has been running for 4 years and a sizeable data set is now available on this group of patients. This is a novel service. Research and evaluation of this service will add to the understanding of how to configure services for this clinically challenging population.